MEDICINAL PLANTS USED AS HOME REMEDIES: A FAMILY SURVEY BY FIRST YEAR MEDICAL STUDENTS - Sewani-Rusike, Constance R; Mammen, Marykutty (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: There is a hierarchical organisation of knowledge in the use of medicinal plants in communities. Medicinal use knowledge starts in the home and is passed on to family members. Next in the hierarchy are neighbours, village elders and finally, traditional healers being the most knowledgeable. For primary health care this hierarchy is actively followed in seeking remedies for ailments. Materials and Methods: This study was a survey of medicinal plant knowledge from family members of 1st year medical students registered at Walter Sisulu University. A total of 206 first year medical students participated in this study in 2010 and 2011. Results: Results revealed 47 species used as home remedies, 32% of which are food plants. Leaves and roots were reported as most commonly used. The top five ailments managed at home were gastrointestinal problems (25 plants), wounds (19 plants), respiratory tract problems (19 plants), infections, including sexually transmitted diseases (19 plants) and pain including headaches (19 plants). Chronic diseases such as hypertension, diabetes, cancer and reproductive ailments also formed a large group of diseases self-managed at home (29 plants). Conclusion: Family members hold knowledge of medicinal plant use. From this study, first year medical students were made aware of the relationship between common ailments and associated home remedies. This study forms a basis for further study of medicinal plants to validate their use as medicinal remedies.